Productive performance and carcass yield of grazing water buffaloes (Bubalus bubalis) and bovine cattle in the growing-fattening stage - Fundora, Orlando; Fernández, D.; Sarduy, Lucía; González, María E. (Cuban Journal of Agricultural Science, 2017)
Twenty water Buffalypso buffaloes and an equal number of Carabao crossbreds, Siboney de Cuba crossbreds and commercial Zebu cattle were used with initial live weights of 170, 184, 201 and 209 kg, respectively for comparing the productive performance, yield and carcass composition. Animals were placed together in a 77 ha grazing area divided in four paddocks. The botanical composition and DM availability of the grassland, individual live weight at the beginning and end of the experiment and weight of the carcasses and its components were measured. An analysis of variance was realized according to a simple classification model with concomitant variable initial live weight. Naturalized pastures constituted 74.7 % and pangola grass 20.9 % of the botanical composition and yielded, as a whole, 2.2 and 0.8 t ha-1 of available DM in the rainy and dry season, respectively. Buffalypso animals gained 624 g daily of live weight, a higher value (P < 0.0001) to that reported for Carabao (506 g) and Zebu (438 g) and Siboney (428 g) cattle. Carcass yield (50.0 and 50.2 %) was lower (P < 0.05) and also that of meat 62.2 and 61.6 % (P < 0.0001) in Buffalypso and Carabao buffaloes, respectively regarding the bovine cattle with values of 51.2 and 51.1 and of 65.4 and 65.0 % in the same order for Siboney and Zebu. However, meat production per surface unit tended to increase in Buffalypso (78.2 kg.ha-1) regarding the Carabao (67.5 kg.ha-1), the Zebu (67.5 kg.ha-1) and Siboney (64.7 kg.ha-1). It is concluded that in natural pastures Buffalypso had better performance than Carabao and the studied bovines. Key words: buffaloes, performance, yield, grazing